The Utilization of Google Meet in the Physics Curriculum Review Course for Pre-Service Teachers within the PMM Program of Universitas Jambi at Universitas Mataram - Hikmawati; Haerul Pathoni (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
This study aimed to analyze the utilization of Google Meet in the Physics Curriculum Review course for pre-service teachers participating in the Student Exchange Program (Pertukaran Mahasiswa Merdeka or PMM) from Universitas Jambi at Universitas Mataram. This study employed a quantitative approach using a descriptive method. The research subjects consisted of 15 students who participated in online learning during the odd semester of the 2025/2026 academic year. Data were collected through an essay test consisting of 10 items designed to measure students’ Higher Order Thinking Skills at the levels of analysis, evaluation, and creation. The data were analyzed using descriptive statistics, including mean score, minimum score, maximum score, standard deviation, and percentage of learning achievement. The results showed that the students achieved an average score of 86.7, categorized as excellent, with the lowest score of 82.5 and the highest score of 90.0. The highest achievement was found at the analysis cognitive level (C4), followed by evaluation (C5) and creation (C6). These findings indicate that the use of Google Meet in the PMM program effectively supports interactive learning, the development of HOTS, pre-service teacher competencies, and the strengthening of impact-driven campus implementation in higher education.